Life with pets study: lower income veterinary clients' perception of pets' quality of life - Strand, Elizabeth B.; Scoresby, Kristel; Walker, Hannah; Hernandez, Ana; Accornero, Veronica; Messinger, Lori; Linden, Pamela; Ward, Chesney; Knight, Matthew P.; Engelman, Haley; Moore, Kristin; Slater, Margaret Ruth (Frontiers in Veterinary Science, 2024)
Perception of quality of life for cats and dogs of low-income Spanish and English-speaking veterinary clients attending problem focused or routine veterinary visits is an important area of focus for community based veterinary service providers. Using a qualitative approach, 50 New York City based American Society for the Prevention of Cruelty to Animals (ASPCA) veterinary clients completed semi-structured interviews as well as a survey about their perception of life with their pets. Veterinary clients shared both human-animal bond (HAB) related and quality of life (QoL) related factors in their daily experience of life with their pets. Results indicated that this demographic perceives QoL similarly to previous QoL research that either does not report sample demographics or reports sample demographics with more affluence. Moreover, 60% of qualitative excerpts included both HAB and QoL themes and 40% were discretely HAB or QoL. An analog single item 10-point scale measuring veterinary client perception of their pets QoL did not differentiate between sample demographics at a statistically significant level. Finally, pet QoL literature has not traditionally reflected diverse demographic identities of veterinary clients or widely included reliable and valid measures of the human-animal bond (HAB). These results support the importance of measuring the HAB when researching pet QoL and provide evidence that lower-income Spanish and English-speaking veterinary clients are similarly bonded and attentive to their pets as other demographics.